11 Generation of developmental origin-specific vascular smooth muscle cells from human embryonic stem cells. Issue 20 (23rd September 2011) - Cheung, C; Bernardo, A; Trotter, M; Pedersen, R A; Sinha, S
Abstract : Heterogeneity is a hallmark of vascular smooth muscle cell (SMC) development, physiology and pathology. This could be attributed to the diverse embryological origins of vascular SMCs. In order to uncover the molecular mechanisms regulating SMC heterogeneity, there is a need for an in vitro system which allows the study of lineage-dependent differences. We have generated origin-specific SMCs from human embryonic stem cells (ESCs) using chemically defined conditions free of animal-derived components. A step-wise differentiation protocol was implemented. Human ESCs were initially induced to form three populations of distinct developmental lineages, namely the lateral mesoderm, somitic mesoderm and neuroectoderm, then followed by SMC differentiation of these intermediate populations. The derived SMCs were positive for smooth muscle markers at both the RNA and protein levels. Their functional properties were confirmed by calcium signalling and contraction observed in response to vasoconstrictors. Genome-wide analysis revealed unique transcriptional signatures which validated the distinct developmental origins of derived SMCs. Furthermore, our derived SMCs recapitulated the differential cell proliferation response to cytokines as demonstrated in previous studies using cultured aortic SMCs of distinct origins. In conclusion, we have generated an in vitro system which has broad applications in modelling SMC heterogeneity, elucidating mechanisms of SMC development, and vascular regenerative medicine.